Current smoking status as a predictor of cerebral infarction in men: a retrospective cohort study in South Korea - Chang-Mo Oh (BMJ Open, 2021)
Objectives We examined the relationship between duration (pack-year) of smoking and the risk of developing cerebral infarction in Korean men.Design Retrospective cohort study.Setting National Health Insurance Service-National Sample Cohort in Korea.Participants Of 125 743 male participants from the National Health Insurance System undergoing medical health check-up in 2009, 114 377 were included in the final analysis.Primary and secondary outcome measures Development of cerebral infarction according to smoking duration after adjusting for age, body mass index, systolic blood pressure, fasting blood glucose, total cholesterol, γ-glutamyltransferase, estimated glomerular filtration rate, alcohol intake and physical activity.Results During 495 827.3 person-years of follow-up, 1450 incident cases of cerebral infarction developed between 2009 and 2013. The multivariate adjusted HRs (95% CI) for cerebral infarction between groups 2, 3 and 4 by duration of smoking were 1.02 (0.88 to 1.19), 1.36 (1.19 to 1.56) and 1.49 (1.28 to 1.74), respectively. In our secondary analysis by smoking status, the HR (95% CI) of former smokers showed a significant relationship in the unadjusted model but did not show statistically significant associations in the multivariate adjusted model. The HR (95% CI) of current smokers showed significant relationship in both the unadjusted and multivariate adjusted models (p for trend <0.001).Conclusions The study indicates that the prolonged duration of smoking (pack-year) increases the risk of cerebral infarction. Current smoking poses a higher risk for the development of cerebral infraction than former smoking among Korean men, indicating that current smoking cessation would be more protective.